2020
DOI: 10.1007/s11368-020-02571-w
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide contamination of the upper Elbe River and an adjacent floodplain area

Abstract: Purpose Pesticide contamination of river waters is a global problem, and therefore, authorities regularly monitor the water quality status. Especially, flood events might transport large pesticide loads downstream and impact adjacent areas such as sensible floodplain environments by deposing particle bound pesticides or by contaminating the environments by dissolved substances directly. Unfortunately, only little attempts were made to quantify the pesticide pollution of such environments, as the monitoring of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 49 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…Atrazine and its metabolites indicate a long‐term contamination because atrazine was banned in the European Union in 2003 but is still measured in urbanized rivers (Karlsson et al, 2020). Chlortoluron presence is consistent with its use on wheat at this period of the year (late February/March; Botta et al, 2012), while tebuconazole levels in the effluent can be explained by applications on rooftops as a fungicide (Paijens et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Atrazine and its metabolites indicate a long‐term contamination because atrazine was banned in the European Union in 2003 but is still measured in urbanized rivers (Karlsson et al, 2020). Chlortoluron presence is consistent with its use on wheat at this period of the year (late February/March; Botta et al, 2012), while tebuconazole levels in the effluent can be explained by applications on rooftops as a fungicide (Paijens et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Pesticide concentrations in the winter season were found to be higher compared with that in the summer season. Karlsson et al (2020) reported the concentrations of pesticide in the Elbe River, Germany. Concentration of atrazine was 270 ng/L, terbuthylazine (which was an alternative for atrazine after getting banned) was 340 ng/L, and metazachlor was 290 ng/L, and metolachlor was found to be 270 ng/L.…”
Section: River and Lake Watermentioning
confidence: 99%
“…The pesticide atrazine (AT) has been banned in Europe in 2004. However, AT and its metabolites are still found in soils and groundwater in potentially harmful concentrations (Jablonowski et al, 2009;Karlsson et al, 2020;Vonberg et al, 2014). In natural environments, AT undergoes abiotic (L opez-Muñoz et al, 2011) and biotic (Udikoviç-Koliç et al, 2012) degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Several bacterial guilds have been observed to metabolise AT (as a carbon source (Ehrl et al, 2019;Kundu et al, 2019), nitrogen source (Sharma et al, 2019) or both (Udikoviç-Koliç et al, 2012), leading to an accumulation of intermediate metabolites. Most commonly, these metabolites are hydroxyatrazine (HY) (Karlsson et al, 2020;Smith et al, 2005;Smith & Crowley, 2006), deisopropylatrazine (DIA) and deethylatrazine (DEA) (Meyer et al, 2014;Ngigi et al, 2012;Zhang et al, 2017). Several different (and possibly simultaneously occurring) AT degradation pathways can lead to the formation of identical metabolites.…”
Section: Introductionmentioning
confidence: 99%